PENGARUH LATIHAN VISUALISASI DAN KEPERCAYAAN DIRI TERHADAP PRESTASI ATLET UKM PANAHAN UNNES - Elhaqe, Qintarazany Marayattaqiezza (Unnes Journal of Sport Sciences, 2021)
Mental training must be essential for archery athletes as archery is an individual sport. However mentaltraining is still being neglected in any archery training program. The purpose of this research is todetermine the effect of visualization training and confidence on the achievement of athletes of studentactivity unit in UNNES. This research is using an experimental research with One Group Pretest andPosttest design. The instrument used is confidence questionnaire and archery score result test. Theresearch subject is nine archery athletes of student activity unit in UNNES. Data analysis technique usesregression test and paired sample t-test. The result of regression test, the value (sig) 0,009 < 0,05 and thepaired sample t test archery score results is t count 2,573 > t table 1,860 with significant level 0,033 <(0,05). As for the self confidence data the value t count 4,203 > t table 1,860 with significant level is 0,003< 0,05. Based on calculation, it is concluded that 1) there is an effect of visualization exercises on athleteachievement, 2) there is increase in self confidence on achievement results in archers. Advice: 1) for archerswho have low self confidence level and score test result can be fixed by using visualization exercises, 2) forcoach to pay more attention to the form of mental training, 3) to researchers can do research with a widersamples and add comparison variables.